CLINICAL PHARMACOLOGICAL APPROACH TO THE USE OF DRUGS AFFECTING HEMOSTASIS IN CHILDREN - Parpieva Salima Bokijonovna (Scholar Express Journals, 2024)
The paper examines the safety and efficacy of using a domestic hemostatic agent, recombinant activated factor VII, coagulagil VII, and prothrombin complex concentrate, prothromplex-600 (Baxter, Austria), in neonatal and pediatric cardiac surgery. The study included 56 children aged 7 days to 5.5 years, who underwent artificial circulation surgery for congenital heart defects. Clinical and laboratory data indicate that coagulagil VII and prothromplex-600 are effective in stopping bleeding.
Keywords: Bleeding; prothrombin complex concentrates; recombinant activated factor VII